A expansão do ensino superior privado em Alagoas: um panorama pós-LDB - Florêncio, Tatiana Magalhães (2007)
This study aims at investigating the process of expanding the higher education in the state of Alagoas, having as its starting point the law 9.394/96 (Lei de Diretrizes e Bases da Educação Nacional) We adopt the historical/ dialectic materialism method in order to analyze the inner relations evolving the phenomenon. From that perspective, we consider the materiality of social relations in the capitalist society to explain the essence of such local expansion. Having the referred theoretical support, we therefore analyse the educational politics within the neo-liberal Brazilian state and its consequences concerning Alagoas. The whole process has been observed regarding data from Censo de Ensino Superior and also from national and local speeches, through significant utterances, specially those taken from interviews with the former Education Minister Paulo Renato Souza and leaders/owners of five different private educational institutes, which were founded after the upsurge of LDBEN. To stablish this relationship between the objective and simbolic dimensions on the phenomenon, we will be working with Discourse Analysis (DA), from the French research line. We conclude then that the higher education market in Alagoas nowadays represents a cultural conflict concerning the institutions managament and at the same time it follows the trend of higher education mercantilism. We also argue that the local socioeconomic reality singles out contradictions as to the own maintenance of this market/field, however, its growth takes place through a strategy of market expansion in the Northeast, supported by the ideology that preaches higher education as essential to employment. With that purpose, the market bets on the continuity of such educational politics which does not invest in the broadening of the public space and also that guarantees the institutions sustainability via financing needy students, in other words, reducing even more the frontiers between the public and the private.